1996
DOI: 10.1108/02686909610107960
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of social auditing in corporate enterprises: a study of the Indian corporate sector

Abstract: Argues that social auditing has a key importance as there is a growing awareness among corporate sector enterprises that every such enterprise should contribute towards the social goals. Attempts to assess the social performance of a corporate enterprise (Steel Authority of India Limited) in terms of costs incurred by the enterprise considered against the benefits to the recipients. There is need to have regular audit of social accounts on the basis of which the comparative social performance of the corporate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 2 publications
0
11
0
1
Order By: Relevance
“…() report that the Cement Corporation of India produced a complete set of social accounts, including a social balance sheet and income statement, for 1981, in accordance with the ABT model. Batra () studies various model formats for corporate social reporting and emphasises the urgent need for social auditing. Considering the diverse range of activities under the CSR umbrella and diversity of motives behind CSR, it is challenging to design an effective standard instrument.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…() report that the Cement Corporation of India produced a complete set of social accounts, including a social balance sheet and income statement, for 1981, in accordance with the ABT model. Batra () studies various model formats for corporate social reporting and emphasises the urgent need for social auditing. Considering the diverse range of activities under the CSR umbrella and diversity of motives behind CSR, it is challenging to design an effective standard instrument.…”
Section: Discussion and Analysismentioning
confidence: 99%
“…First, this study examines its data from the perspective of economic consequences. Second, recent studies on CSR conducted in the third world countries have used it as guidelines for their research (Batra, 1996;Imam, 2000;Raman, 2006). Third, as outlined in the previous section, the Indian companies do not adopt the international standards (such as Global Reporting Initiative's Sustainability Reporting Guidelines) to report on their social activities, which do not allow the study to use these contemporary guidelines.…”
Section: Csr and Software Industry In The Indian Contextmentioning
confidence: 99%
“…As previously noted, the two categories, namely human resources and community development were selected for this study. Based on the recommendations of the NAA committee and other prior studies (Batra, 1996;Imam, 2000) each category is identified by a number of attributes. Human resource category included training, employee numbers, career development, equity issues, compensation plans, employee benefits, and safety.…”
Section: Reporting Practices Disclosed In Annual Reportsmentioning
confidence: 99%
“…Despite this, however, research on social and environmental accounting in emerging and less developed economies is scarce (Belal & Owen, 2007;Islam & Deegan, 2008), although there are a number of exceptions such as a small, but increasing, knowledge base with regard to India (Batra, 1996;Hegde, Bloom, & Fuglister, 1997;Singh & Ahuja, 1983) and Bangladesh (Belal & Roberts, 2010;Belal, 2008;Belal & Owen, 2007;Islam & Deegan, 2008). Nevertheless it is still true to say that we know very little about social and environmental accounting practices in many of the emerging and less developed economies.…”
Section: Introductionmentioning
confidence: 99%